Dewetting of Pt Nanoparticles Boosts Electrocatalytic Hydrogen Evolution Due to Electronic Metal-Support Interaction - Harsha, Shreyas; Sharma, Rakesh K.; Dierner, Martin; Baeumer, Christoph; Makhotkin, Igor; Mul, Guido; Ghigna, Paolo; Spiecker, Erdmann; Will, Johannes; Altomare, Marco (Advanced Functional Materials, 2024)
Solid-state dewetting is the heat-induced agglomeration of thin metal films into defined nanoparticles (NPs). Dewetted Pt nanoparticles are investigated on F-doped SnO2 (FTO) substrates as model binder-free electrodes for the hydrogen evolution reaction (HER). Dewetting of Pt films into particles exposes the FTO substrate and the metal/support (Pt-FTO) contact line. Despite the decrease in Pt electrochemical surface area (ECSA) upon dewetting, dewetted NPs show a >3-fold increase in ECSA-normalized HER activity compared to as-deposited nanocrystalline Pt films. Electrodes designed with dewetted Pt NPs of different sizes show that the HER activity does not only correlate with the ECSA but also increases with increasing the Pt-FTO contact line length. The smaller the NPs, the larger the Pt-FTO contact line, and the higher the activity. This effect is ascribed to electronic metal-support interaction (EMSI), due to electron transfer from FTO to Pt. It is proposed that EMSI effects alter the electronic structure of Pt sites near the Pt-FTO contact line, facilitating the H2 evolution kinetics. When NPs are a few nm-sized, a large mass fraction of Pt is affected by EMSI, resulting in a further increase of HER activity compared to NPs ≥10 nm despite the lower ECSA.
CRIS-Team Scopus Importer:2024-08-23
Keywords: electrocatalysis; electronic metal-support interaction; hydrogen evolution reaction; nanoparticles; platinum; solid-state dewetting